Heterogeneity of Ara h Component-Specific CD4 T Cell Responses in Peanut-Allergic Subjects - Renand, Amedee; Farrington, Marry; Whalen, Elizabeth; Wambre, Erik; Bajzik, Veronique; Chinthrajah, Sharon; Nadeau, Kari C.; Kwok, William W. (Frontiers in Immunology, 2018)
Understanding the peanut-specific CD4 T cell responses in peanut-allergic (PA) subjects should provide new insights into the development of innovative immunotherapies for the treatment of peanut allergy. Although peanut-specific CD4 T cells have a TH2 profile in PA subjects, the immunogenicity of different Ara h components in eliciting specific CD4 T cell responses and the heterogeneity of these Ara h-reactive TH2 cells remains unclear. In this study, we investigated Ara h 1, 2, 3, 6, and 8-specific T cell responses in PA and sensitized non-peanut-allergic (sNPA) subjects, using the CD154 upregulation assay and the class II tetramer technology. In the PA group, T cells directed against Ara h 1, 2, 3, and 6 have a heterogeneous TH2 phenotype characterized by differential expression of CRTH2, CD27, and CCR6. Reactivity toward these different components was also distinct for each PA subject. Two dominant Ara h 2 epitopes associated with DR1501 and DR0901 were also identified. Frequencies of Ara h-specific T cell responses were also linked to the peanut specific-IgE level. Conversely, low peanut-IgE level in sNPA subjects was associated with a weak or an absence of the allergen-specific T cell reactivity. Ara h 8-specific T cell reactivity was weak in both PA and sNPA subjects. Thus, peanut-IgE level was associated with a heterogeneous Ara h (but not Ara h 8)-specific T cell reactivity only in PA patients. This suggests an important immunogenicity of each Ara h 1, 2, 3, and 6 in inducing peanut allergy. Targeting Ara h 1-, 2-, 3-, and 6-specific effector-TH2 cells can be the future way to treat peanut allergy.